Sun exposure and visual field damage among children on the Adriatic Island Rab : possible initial risk factor in development of age-related Macular degeneration - Vojniković, Božidar (Array, 2009)
Abstract: The Adriatic Island Rab, situated in the northern part of the Croatian sea, is more strongly exposed to sunlight (especially from May to October) than the other parts of Croatia and most of the European countries. As consequences of higher solar radiation, significant percentage of Pseudoexfoliation of lens capsula occurs in 15% and fundus picture of AMD (Age-Related Macular Degeneration) in 18% of agriculturalists and fishermen (45–70 years old). We previously presented the first clinical study showing that in AMD the peripheral visual field is also damaged. In this clinical study we examined 68 children (8–15 years old), including following procedures: vision correction, slit lamp examination, visual field in technic of isopters and profile quantitative perimetry (meridian retinal thresholds examination) using Kowa automated perimeter. In 15% of examinees we found strictly foveal »degeneration«, and changes of visual fields: higher meridian thresholds and typical changes with invagination of isopters. It is very interesting that these children with damaged visual field and fundus picture do not protect their eyes from the sunlight during summertime. We suggest the possibility of the influence of higher sun radiation as one of the risk factors in the earlier development of future AMD